Does green HR management attention foster sustainability? A quantile-based analysis - Alruwaili, Naif Fawzi (Zielona Góra: Faculty of Economics and Management Press)
This study investigates the role of Green Human Resource Management (HRM) attention in fostering corporate sustainability. By using a quantile regression (QR) model, I explore Green HRM both as an aggregate measure and across three levels such as operational, managerial, and strategic to provide nuanced insights into how these practices influence sustainability under varying market conditions. The findings reveal that Green HRM attention enhances sustainability at higher quantiles (0.75 to 0.95), underscoring its effectiveness during bullish market phases. Notably, operational-level Green HRM has a significant impact at lower quantiles (0.2), reflecting its relevance during unfavorable market conditions.
Keywords: sustainability; S&P 500 ESG Index; quantile regression; Green HR Management